Effects of Toxic Chemical on Aquatic Biota of Jabi Lake - Motunrayo, A. M.; Makpo, J. K.; Banyigyi, H. A. (Sahel Journal of Life Sciences FUDMA, 2024)
Aquatic ecosystems play a vital role in global biodiversity and ecological productivity, with lakes being some of the most diverse environments. However, increasing anthropogenic activities, such as agriculture, industry, mining, and urban effluents, contribute to heavy metal pollution in these ecosystems. While metals are essential nutrients in low concentrations, they become toxic when exceeding regulatory limits. This study investigated heavy metal contamination in Jabi Lake and its tributaries to assess pollution levels and provide information for sustainable resource management. Seven sampling stations were selected, including three in tributaries, one at the confluent, and three within the lake, to evaluate the chemical and biological characteristics of the water. Standard procedures were employed to analyse data collected over the study period, with statistical tests performed at a 95% significance level (p ≤ 0.05). Findings revealed heavy metal concentrations in water, with copper (0.01–0.35 mg/L), iron (0.02–3.59 mg/L), lead (0.01–0.20 mg/L), zinc (0.01–0.031 mg/L), chromium (0–0.07 mg/L), and cadmium (0–0.4 mg/L). Iron levels exceeded the regulatory limit of 1.0 mg/L, raising concerns about its potential health risks. Heavy metals, including cadmium, iron, and zinc, were also detected in fish species such as Clarias gariepinus, Pseudotolithus senegalensis, and Oreochromis niloticus. The high iron concentrations in both water and fish tissues highlight significant risks to consumers’ health. A systematic management approach is necessary to ensure the sustainability of Jabi Lake’s fishery resources and surrounding environment.